Functional Unit Construction for Heat Storage by Using Biomass-Based Composite - Su, Jingtao; Weng, Mengman; Lu, Xiang; Xu, Weihao; Lyu, Sha; Liu, Yidong; Min, Yonggang (Frontiers in Chemistry, 2022)
How to construct a functional unit for heat storage by using biomass materials is significant for the exploration of phase change materials (PCMs). In this work, we try to design and construct a functional unit for heat storage by employing a vacuum impregnation method to prepare sugarcane-based shape stabilized phase change materials (SSPCMs) for improving the thermal conductivity of phase change materials (PCMs) and preventing the liquid state leakage of PCMs. The morphologies of the prepared materials are characterized by Scanning electron microscope (SEM) as containing a unique channel structure which is viewed as the key factor for heat storage. X-ray diffractometry (XRD), Fourier transform infrared spectroscopy (FT-IR), and thermogravimetric analysis (TGA) were used to characterize the prepared materials. The results indicated that no chemical reaction occurred between PEG and sugarcane-based biomass during the preparation process and SSPCMs showed great thermal stability. Their thermal properties are measured by using the differential scanning calorimetry (DSC) characterization and show a high melting enthalpy of 140.04 J/g and 94.84% of the relative enthalpy efficiency, illustrating the excellent shape stabilized phase change behavior. Moreover, the highest thermal conductivity of SSPCMs is up to 0.297 W/(mK), which is 28.02% higher than that of the pristine PEG. The excellent capability for thermal energy storage is attributed to the directional thermal conduction skeletons and perfect open channels and the unique anisotropic three-dimensional structure of the SSPCMs. Hence, the unique structure with PEG is testified as the functional unit for heat storage. Comprehensively considering the excellent properties of sugarcane-based materials—providing cheap raw materials via green preparation—it is conceived that sugarcane-based materials could be applied in many energy-related devices with reasonable function unit design.